MODEL PEMBELAJARAN PERSEORANGAN DAN PEMBELAJARAN KELOMPOK KECIL (PPKK) DAN KRITERIA PENILAIAN - MUSTAMIN IDRIS (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The study is aimed at obtaining information about the effect of assessment criteria and models of instruction towards students’ achievement in mathematics. The research applied cluster random sampling and the 2 x 2 factorial designs. Findings of this study showed that: students who received Analytic Assessment achieved higher achievement than those who received Holistik Assessment, students who were taught through model of PPKK in which students were gathered in small group and individuals achieved higher achievement than those through Conventional Instructional method, assessments criteria and instructional model significantly affected students’ achievement differences in mathematics, students who were given PPKK and at the same time Analytic Assessment achieved lower achievement than those Holistik Assessment, students who were taught by using Conventional teaching and learning model in Holistik Assessment achieved higher achievement than those Holistik Assessment, students who were given Analytic Assessment and at the same time PPKK model achieved higher achievement than those in Conventional Instruction method, students who were given Holistik Assessment and at the same time PPKK model achieved higher achievement than those in Conventional Instruction model.